2013
DOI: 10.1080/00028487.2013.829121
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Molecular Assay to Detect Predation on an Endangered Fish Species

Abstract: Mastication, digestion, and rapid evacuation rates make visual identification of larval fish remains in the digestive tracts of predatory fishes problematic. Recent advances in molecular technology, however, have increased the likelihood of identifying remnants of partially digested larval prey, thereby enabling assessment of predator impacts on local populations. Conducting controlled laboratory experiments, we evaluated the utility of quantitative polymerase chain reaction (qPCR) for identification of Razorb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Diet items could be identified to similar taxonomic levels as morphological diet analyses, with the potential for metabarcoding to have even higher taxonomic resolution as more sequences and longer reads become available. Metabarcoding also revealed that predator diets were more diverse than previously thought, detecting predation on taxa such as larval fishes and rotifers that are unlikely to be accounted for using morphological diet analysis (Carreon‐Martinez et al, ; Hunter, Taylor, Fox, Maillard, & Taylor, ; Ley et al, ).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…Diet items could be identified to similar taxonomic levels as morphological diet analyses, with the potential for metabarcoding to have even higher taxonomic resolution as more sequences and longer reads become available. Metabarcoding also revealed that predator diets were more diverse than previously thought, detecting predation on taxa such as larval fishes and rotifers that are unlikely to be accounted for using morphological diet analysis (Carreon‐Martinez et al, ; Hunter, Taylor, Fox, Maillard, & Taylor, ; Ley et al, ).…”
Section: Discussionmentioning
confidence: 98%
“…Metabarcoding also revealed that predator diets were more diverse than previously thought, detecting predation on taxa such as larval fishes and rotifers that are unlikely to be accounted for using morphological diet analysis (Carreon-Martinez et al, 2011;Hunter, Taylor, Fox, Maillard, & Taylor, 2012;Ley et al, 2014).…”
Section: Con Clus Ionsmentioning
confidence: 90%
See 1 more Smart Citation
“…Larval sucker survival in Klamath Lake was negatively associated with Fathead Minnow density and interactions with water depth and percent vegetation (Markle and Dunsmoor 2007). Both Mosquitofish and Green Sunfish readily consumed larval Razorback Suckers Xyrauchen texanus in a controlled environment (Ley et al 2014). Interactions of larval June Sucker with the littoral species of Utah Lake need to be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…Advances in molecular techniques have enabled the successful identification of DNA from prey contained in the gut contents of predatory fishes after the prey are no longer visually identifiable (Rosel and Kocher 2002;Carreon-Martinez et al 2011;Hunter et al 2012;Ley et al 2014;Brandl et al 2016). Utilizing quantitative PCR (qPCR), Ley et al (2014) identified Razorback Sucker DNA in the gut contents of 87.5% of Green Sunfish Lepomis cyanellus at 2 h postconsumption and 75% of Green Sunfish at 12 h postconsumption. The Ley et al (2014) study validated the use of qPCR for identifying Razorback Sucker larvae in the gut contents of nonnative fishes and demonstrated a greatly extended timeline over which larvae could be positively identified in fish stomachs.…”
mentioning
confidence: 99%